2022
DOI: 10.1002/adhm.202200271
|View full text |Cite
|
Sign up to set email alerts
|

The Technological Advancement to Engineer Next‐Generation Stent‐Grafts: Design, Material, and Fabrication Techniques

Abstract: Endovascular treatment of aortic disorders has gained wide acceptance due to reduced physiological burden to the patient compared to open surgery, and ongoing stent-graft evolution has made aortic repair an option for patients with more complex anatomies. To date, commercial stent-grafts are typically developed from established production techniques with simple design structures and limited material ranges. Despite the numerous updated versions of stent-grafts by manufacturers, the reoccurrence of device-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 225 publications
(399 reference statements)
0
9
0
Order By: Relevance
“…In recent years, efforts have been made to develop new stent graft devices by focusing on smart or reactive materials designed to have one or more properties that can be transformed in a controlled manner by external stimuli such as stress, humidity, electric or magnetic fields, light, temperature, pH or chemical compounds [ 97 ]. In this regard, shape memory materials (SMM) have been identified that can be transformed and fixed in a temporary form, recovering their original shape when subjected to an appropriate stimulus [ 98 ].…”
Section: New Generation Stent Graftmentioning
confidence: 99%
“…In recent years, efforts have been made to develop new stent graft devices by focusing on smart or reactive materials designed to have one or more properties that can be transformed in a controlled manner by external stimuli such as stress, humidity, electric or magnetic fields, light, temperature, pH or chemical compounds [ 97 ]. In this regard, shape memory materials (SMM) have been identified that can be transformed and fixed in a temporary form, recovering their original shape when subjected to an appropriate stimulus [ 98 ].…”
Section: New Generation Stent Graftmentioning
confidence: 99%
“…15,16 The most common method to regulate the radial force is to adjust the braiding parameters and/or structure of the stent, in which the braiding parameters mainly include the diameter of the stent, the diameter of the monofilament, and the braiding angle. [17][18][19][20][21] In addition, structural design can also be optimized to improve supportability. Innovative methods about flow channels, such as adding new flow channels in axial, circumferential, and helical directions, have always been considered to obtain better structural stability.…”
Section: Introductionmentioning
confidence: 99%
“…To date, researchers have conducted a lot of research on supportability, especially for polymer stents with weak mechanical properties 15,16 . The most common method to regulate the radial force is to adjust the braiding parameters and/or structure of the stent, in which the braiding parameters mainly include the diameter of the stent, the diameter of the monofilament, and the braiding angle 17–21 . In addition, structural design can also be optimized to improve supportability.…”
Section: Introductionmentioning
confidence: 99%
“…By adopting interferometric principles, optical coherence tomography (OCT) has been increasingly developed and commercialized in the biomedical area. Furthermore, the biomedical devices such as stents, implants, wires and catheters need the surface coating to protect the devices from corrosion as well as infection from disease, and the coated film should be carefully inspected to avoid unexpected hazards [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…By adopting interferometric principles, optical coherence tomography (OCT) has been increasingly developed and commercialized in the biomedical area. Furthermore, the biomedical devices such as stents, implants, wires and catheters need the surface coating to protect the devices from corrosion as well as infection from disease, and the coated film should be carefully inspected to avoid unexpected hazards [17,18]. Typically, a scanning electron microscopy (SEM) and a transmission electron microscopy (TEM) have been widely used to inspect the metallic, organic and inorganic film structures with high precision [19,20].…”
Section: Introductionmentioning
confidence: 99%